Comparison of Air Force, Army, and Navy Emergency Medical Technician Candidates' Performance on the National Registry Cognitive Examination. Issue 11 (4th December 2020) - Mercer, Christopher B; Cash, Rebecca E; Rivard, Madison K; Chrzan, Kirsten; Harper, Stephen; Walrath, Benjamin; Carmichael, Jennie L; Panchal, Ashish R
ABSTRACT: Introduction: Military medics function similarly to civilian emergency medical technicians (EMTs); however, they perform their emergency medical care in combat zones and military treatment facilities. Both civilian and military EMTs must take and pass the National Registry of EMT's cognitive examination to be certified as a Nationally Registered EMT; however, there is a discrepancy in requirements for obtaining and maintaining National EMT Certification between the military branches of the DoD. In our study, we aimed to compare the performance of the U.S. Air Force (USAF), U.S. Army (USA), and U.S. Navy (USN) EMT candidates on the National EMT Certification cognitive examination from 2015 to 2017. Materials and Methods: We performed a cross-sectional analysis of the National Registry of EMT's database for the examination results of all military EMT candidates who attempted the National EMT Certification cognitive examination between January 1, 2015, and December 31, 2017. First and cumulative third attempt pass rates and cognitive performance from mean ability estimates (MAEs) on the examination were assessed. Descriptive statistics were calculated and comparisons between branches with regard to passing rates and MAEs were made using chi-square tests and ANOVA, respectively, at the alpha level of 0.05. Results: During the 3-year study period, a total of 3, 642 USAF, 14, 050 USA, and 1, 187 USN candidates attempted the cognitive examination one or more times. The USA candidates demonstrated the highest first attempt pass rates (2015: 78%; 2016: 78%; and 2017: 81%) followed by the USAF candidates (2015: 58%; 2016: 62%; and 2017: 64%) and the USN candidates (2015: 41%; 2016: 56%; and 2017: 62%). The cumulative third attempt pass rates followed a similar trend (e.g., USA: 2015: 94%; 2016: 95%; and 2017: 96%). These differences by branch were statistically significant for each year ( P < .001). The overall test MAE scores also differed by branch, but only the USN candidates' MAE scores differed by year. The USA candidates demonstrated the highest MAE from 2015 to 2017 (523) followed by the USAF (489) and the USN (464) candidates. The overall test MAE scores for the USN candidates improved over the study period (2015: 449; 2016: 475; and 2017: 479, P < .001). Conclusion: Military EMT candidates had different performances on the EMT cognitive examination between branches. The USA candidates demonstrated higher pass rates and cognitive performance on the examination compared to their counterparts from the USAF and USN from 2015 to 2017. Further work should be directed at defining the cause of the differences in military EMT candidate performance and determining the characteristics that impact these differences.